Specificity of 14-3-3 isoform dimer interactions and phosphorylation. (August 2002) - Aitken, A.; Baxter, H.; Dubois, T.; Clokie, S.; Mackie, S.; Mitchell, K.; Peden, A.; Zemlickova, E.
Abstract : Proteins that interact with 14-3-3 isoforms are involved in regulation of the cell cycle, intracellular trafficking/targeting, signal transduction, cytoskeletal structure and transcription. Recent novel roles for 14-3-3 isoforms include nuclear trafficking the direct interaction with cruciform DNA and with a number of receptors, small G-proteins and their regulators. Recent findings also show that the mechanism of interaction is also more complex than the initial finding of the novel phosphoserine/threonine motif. Non-phosphorylated binding motifs that can also be of high affinity may show a more isoform-dependent interaction and binding of a protein through two distinct binding motifs to a dimeric 14-3-3 may also be essential for full interaction. Phosphorylation of specific 14-3-3 isoforms can also regulate interactions. In many cases, they show a distinct preference for a particular isoform(s) of 14-3-3. A specific repertoire of dimer formation may influence which of the 14-3-3-interacting proteins could be brought together. Mammalian and yeast 14-3-3 isoforms show a preference for dimerization with specific partners in vivo.